Hubungan Gaya Hidup dengan Kejadian Hipertensi pada Usia Dewasa 20 – 60 Tahun di Wilayah Kerja Blud UPT Puskesmas Pahandut Kota Palangkaraya Tahun 2022: The Correlation of Lifestyle and the Incident of Hypertension in Adults 20-60 Years Old in the Work Area of the Blud UPT Puskesmas Pahandut Palangka Raya City in 2022 - Abraham Panarung; Mariaty A. Sungkai; Melisa Frisilia (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Hypertension is an increase in systolic blood pressure of more than 140 mmHg and diastolic blood pressure of more than 90 mmHg. One of the risk factors for hypertension is an unhealthy lifestyle that affects adults. The purpose of this study was to determine the correlation of lifestyle and the incident of hypertension in adults in the work area of BLUD UPT Puskesmas Pahandut, Palangka Raya. The method used is accidental sampling. The design of this study uses analytical descriptive research with a cross-sectional approach. The samples taken were from79 hypertensive patients who visited the Pahandut Health Center. The data of this study were taken using questionnaires. After tabulating, the data were analyzed univariately and bivariately analysis using the Chisquare test. The results of the study showed that the significance value of p-value = 0.000 (0.05). This shows that there is a correlation of lifestyle and the incident of hypertension in adults in the BLUD UPT Pahandut Health Center work area, Palangka Raya City. The advice given is that people's lifestyles can be well maintained by doing physical activity, maintaining a diet to reduce smoking and drinking coffee habits.